ANALISIS SEMIOTIKA PEMASARAN OSWALD DENGAN SISTEM CONSUMER BRANDSCAPE PADA IKLAN MS GLOW FOR MEN #SEMUAJUGABISA - Linna Friska; Lasmery Rosentauly Maissalinya Girsang (Commed : Jurnal Komunikasi dan Media, 2022)
Advertising has the power to change the mindset of an exposed audience. Therefore, advertisements must attract the attention of audiences by displaying advertising visualizations that are packaged in a unique way but cannot be separated from the main message to be conveyed to the audience. The more unique an ad will get a lot of responses from the audience and it is possible that the ad will go viral. This study aims to reveal the meaning of MS Glow For Men's viral advertisement titled #SemuaJugabisa. The virality of the MS Glow For Men ad on social media Instagram is due to the presentation of unusual visualizations and an advertising story wrapped in comedy featuring well-known comedians in Indonesia, Babe Cabiita and Marshel Widianto who are also brand ambassadors of MS Glow For Men. The results of the research through Oswald's Marketing Semiotics analysis with the Consumer Brandscape system reveal the meaning behind the MS Glow For Men #SemuaJugabisa advertisement, where MS Glow For Men has the motivation to break the concept of beauty standards for brand ambassadors, advertising stars and all men in using facial care products. So that the goal of MS Glow For Men is achieved, which is to make all men have a well-groomed, clean and radiant face or what is known as 'glowing'. Keywords: Semiotics, Oswald Marketing Semiotics, Consumer Brandscape, Beauty Standard, Men's Skincare